Pricing Wind Power Uncertainty in the Electricity Market - Luis Ramirez-Burgueno; Yuanrui Sang; Yingying Zheng (IEEE Access, 2023)
The volatile and intermittent nature of renewable energy sources (RES) has a critical impact on electric power grid operations. However, there still lacks a model to price the uncertainty of renewable energy in electricity markets. This paper aims to propose a model to quantify the impact of the uncertainty of RES on the power system operating costs in an electricity market environment considering the use of flexible ramping (FR) products, compensation for wind power curtailment, and the cost for flexible load curtailment, and thus offer a method to price the uncertainty of RES. The model is based on a stochastic optimization model for power system operations considering FR products, and the uncertainty cost is calculated by comparing the dispatch cost as well as the compensation for wind power curtailment and load curtailment with and without uncertainties. The method was implemented on a modified RTS-96 test system with a high penetration of wind energy, and the uncertainty of wind power output was represented using three different distributions, namely, Gamma, Weibull, and Rayleigh. Results show that the uncertainty of wind power increases power system operating costs, and different uncertainty modeling can affect the pricing of wind power uncertainty by up to 5%. This shows that there is a need for system operators to choose the appropriate distribution to model wind power uncertainty when pricing wind power uncertainty.